PENGARUH CITRA DAN KESADARAN MEREK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA TEH HIJAU DALAM KEMASAN SIAP MINUM â€œNU GREEN TEAâ€ UB BAROKAH - Budianto, Aris; Yosepha, Sri Yanthy (JURNAL ILMIAH M-PROGRESS, 2019)
The purpose of this study is to know the influence of image, brand awareness on consumer purchasing decisions. This study uses a descriptive research which isa research describes the objects related to the decision taking generally.In this study, a researcher takes 50 respondents as a sample by using accidental sampling which is the consumers who do purchasing decision in Nu Green Tea, should answer the questionnaires. Â Â Â Â Â Â  The finding of this study shows two independent variables which are image and brand awareness. Those have positive and significant influenced toward dependent variable that is Nu Green Tea's purchasing decisions. The result of double regression shows all of independent variable (image and brand awareness) give positive influenced toward Nu Green Tea's purchasing decisions. The biggest positive influenced toward Nu Green Tea's purchasing decision is on the brand awareness variable with coefficient 0,934, then it is followed by image variable with coefficient 0,085.Â Keywords: Brand Image, Brand Awareness, and Purchasing Decision.Â